Sensitivity of localization studies performed by various radiologists in the evaluation of parathyroid lesions - Şişman, Pınar; Öz Gül, Özen; Cander, Soner; Şahin, Ahmet Bilgehan; Demirtaş, Çoşkun; Muti, Aybüke; Elbasan, Onur; Saraydaroğlu, Özlem; Ertürk, Erdinç (The European Research Journal, 2018)
Objectives. Preoperative imaging studies are commonly used in the diagnosis of primary hyperparathyroidism to increase the success rate of surgery. In the present study, we aimed to correlate surgical outcomes with the sensitivity of localization studies that were performed by various radiologists. Methods. One hundred eighty-nine patients with preoperative diagnosis primary hyperparathyroidism were included. A total of 174 patients in whom hypercalcemia had been cured by parathyroidectomy, were evaluated retrospectively. In total, 184 lesions were excised from these 174 patients. Ultrasonography (USG) and technetium-99m-methoxy isobutyl isonitrile (99mTc-MIBI) imaging yielded correctly localized lesion in 74 and 108 patients, respectively. Results. The specificity of USG and 99mTc-MIBI imaging were similar (95.9% and 95.0%, respectively). However, the sensitivity was not satisfactory (45.9% for USG, 62.4% for 99mTc-MIBI). The gland size was not significant for the rate of lesion detection by 99mTc-MIBI scan or USG. Significant differences were not observed between the preoperative serum parathormone, serum calcium or 24-hour urine calcium excretion levels and the success rate of localization with either USG or 99mTc-MIBI. Conclusions. Radiologist experience in ultrasonographic parathyroid imaging was found to affect sensitivity. Therefore, surgeons, radiologists and endocrinologists that perform ultrasonographic evaluation should have extensive experience.